The judiciary and the bar (Syariah System) - Ali Mohamed, Ashgar Ali; Ali Tajuddin, Hanifah Haydar (The Malaysian Current Law Journal Sdn Bhd, 2014)
A person entrusted with the administration and enforcement of Syariah must be competent according to the criteria laid down by Allah (SWT) Justice may only be realised through competent and just judges, accurate proof and strong evidence. Allah (SWT) commands that the parties who are involved in a dispute, to act honestly while giving evidence in order to secure or deny a claim. Such persons must consider themselves as witnesses on behalf of Allah (SWT) and His Messenger (SAW) because Islam requires the parties to render justice to those who are entitled to it. There may be instances where the lawyer’s eloquence of argument and speech may influence the adjudicator’s findings in favour of their client but nevertheless justice and righteousness is not on his side. In such a situation, the lawyer had only managed to do evil; what he had won is nothing more than sin, falsehood and hell fire. Hence, this chapter discusses the Syariah judicial, powers of the Chief Syariah Prosecutor, the admission and qualification of Peguam Syarie (Syarie lawyer) and issue of legal representation of a non-Muslim in the Syariah Courts, among others